Inanimate Alice -- do imaginário-virtual ao real - Sibem, Liandra Tomazine (2012)
The present study approaches the point of reading works written in authentic language, in English language, running away from the adaptations and facilitations of texts found in didactic books and, above all, the inclusion of electronic literature in the English language classes. This research, which assumes the qualities and the characteristics of action research, took place with High School students in a private school in the city of Passo Fundo, RS. The chosen narrative, Inanimate Alice, produced in Flash, which characterizes itself for joining several medias, like sound, image and moving image, sound and visual effects and the elements of electronic games, is composed by four episodes. This investigation focuses on the benefits brought by the inclusion of working with hypertext and the several medias, by the usage of the computer connected to the internet, in the classroom, as well as the group work, showing that while a team, the students are able to help and motivate themselves, making possible a bigger wealth in the final results of their papers. Therefore, this research offers the proposal of an activity based on the interactive fiction work mentioned before. In this activity, it happens the creation of hipertextual works produced by the students, organized in groups, based on the four episodes of the narrative